(untitled) (Estudios Gerenciales, 2014)
This paper presents some reflections on strategic response models, in particular the models proposed by Pache, Santos and Oliver, and it evaluates their complementarity and differences, especially regarding the interactions between decision making and the possible strategic responses to institutional demands. It is argued that the theoretical contributions of Pache and Santos can be categorized under the dimension of utility, because they can enhance the potential to operationalize and test the model. However, the reflections made in this paper not only highlight the need to take into account other external and internal factors for the study of strategic responses, but also the integration of different linkages of the decision process with strategic responses to institutional demands.